Visualisasi karakter mainan boneka untuk edukasi seksual anak usia 3-6 tahun - Amelia Margaretha Suprapto; Wyna Herdiana; Florentina Tiffany (Institut Seni Indonesia Yogyakarta, 2026)
Sexual education from an early age is an essential step in equipping children with an understanding of their bodies, personal boundaries, and self-protection from inappropriate behavior. However, delivering this material requires an appropriate approach tailored to the cognitive development of early childhood. This study aims to design an educational doll character as a learning medium for sexual education targeting children aged 3–6 years. A qualitative approach was employed, with data collected through In-Depth Interviews (IDI) and visual studies. Interviews were conducted with seven informants, including child clinical psychologists, parents, early childhood educators, and a children's book illustrator, to explore perspectives on sexual education and suitable visual character designs for young children. The visual study involved analyzing character illustrations from both local and international children's books. The doll character visualization adopts a simple, friendly, and appealing cartoon (chibi) style. The character is designed in two versions—male and female—to provide specific understanding of biological differences and to help children recognize body parts categorized as private areas. These parts are depicted explicitly but not vulgarly, using pastel colors and friendly facial expressions to build emotional closeness with the child.